2003
DOI: 10.1007/s10295-003-0027-3
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of phytase production by solid substrate fermentation

Abstract: The production of phytase by three feed-grade filamentous fungi ( Aspergillus ficuum NRRL 3135, Mucor racemosus NRRL 1994 and Rhizopus oligosporus NRRL 5905) on four commonly used natural feed ingredients (canola meal, cracked corn, soybean meal, wheat bran) was studied in solid substrate fermentation (SSF). A. ficuum NRRL 3135 had the highest yield [15 IU phytase activity/g dry matter (DM)] on wheat bran. By optimizing the supplementation of wheat bran with starch and (NH(4))(2)SO(4), phytase production incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
50
2
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(59 citation statements)
references
References 22 publications
6
50
2
1
Order By: Relevance
“…Products rich in phytase enzyme also contain some other hydrolytic enzymes that favor digestion in non-ruminants. This was reported by Bogar et al (2003) who found alpha amylase, xylanase and others. The supplementation of these enzymes together with phytase contributes to a decrease in the viscosity of food during digestion, amount of loose droppings, increases or mass gain, feed conversion and egg production in the case of poultry (Morales et al, 2011;Romero et al, 2009).…”
Section: Estimation Of Phytase Production By Ssfsupporting
confidence: 61%
See 1 more Smart Citation
“…Products rich in phytase enzyme also contain some other hydrolytic enzymes that favor digestion in non-ruminants. This was reported by Bogar et al (2003) who found alpha amylase, xylanase and others. The supplementation of these enzymes together with phytase contributes to a decrease in the viscosity of food during digestion, amount of loose droppings, increases or mass gain, feed conversion and egg production in the case of poultry (Morales et al, 2011;Romero et al, 2009).…”
Section: Estimation Of Phytase Production By Ssfsupporting
confidence: 61%
“…The significance level of each variable was determined by Pareto charts, and statistical analyses of the data were carried out using analysis of variance (ANOVA) and Student´s t-test mean comparison test (p<0.05) (Statistica® 7, Statsoft, 217 Tulsa, OK, USA). The Box-Behnken design (BBD) was used to investigate the relationship between variables of medium components, and to optimize their concentrations for the best yield of phytase enzyme production in SSF, using A. niger (Bogar et al, 2003;Mittal et al, 2011). In experiments of the present study, four factors at three levels of variations were defined (Table 5).…”
Section: Experimental Design To Optimize the Medium Selected And Statmentioning
confidence: 99%
“…A. ficcum NRRL 3135 produced 25 U gds -1 using wheat bran as substrate (Bogar et al, 2003), and higher phytase yield (130 U.gds -1 ) was obtained using released meal by an A. niger A-98 locally isolated (El-Batal and Karem, 2001). …”
Section: Resultsmentioning
confidence: 99%
“…Sedangkan A. niger menghasilkan enzim fitase paling tinggi setelah 3 hari inkubasi pada media yang mengandung 1 g/L gum, pada suhu 30°C (Papagianni et al, 2001). Aspergillus ficuum NRRL 3135, Mucor racemosus NRRL 1994 dan Rhizopus oligosporus NRRL 5905 menghasilkan enzim fitase tertinggi pada medium yang mengandung tepung canola, jagung, kedelai, dan dedak pada suhu 26 ± 1°C (Bogar et al, 2003). Hal tersebut menunjukkan suhu sekitar 30°C cukup optimal untuk memproduksi enzim fitase.…”
Section: Kondisi Optimum Produksi Fitase Pada Ssfunclassified